PRO-ACTIVE LEGISLATIVE TARGETS - 1990 INDEX PRO-ACTIVE PROPOSAL OKLAHOMA HIRING DISCRIMINATION (Tufts Archival Research Center, 2007)
Index of legislative targets by state and a report discussing a pro-active proposal in Oklahoma regarding hiring discrimination. Seeks to prohibit hiring and firing of individuals based on tobacco use.